Antibacterial heat-insulating soft porcelain decoration material and preparation method thereof
Patent Information
- Application Number
- CN202611061599.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明提供了一种抗菌型保温软瓷装饰材料及其制备方法,所制备的软瓷装饰材料不仅具有优异的抗菌性能及保温性能,还具有很好的力学性能,有效地保证了其品质的同时,也在一定程度上解决了其因微生物侵蚀而导致使用寿命缩短的技术问题
1、本发明以聚丙烯腈、保温剂及聚苯乙烯-丙烯腈共聚物等为原料,通过经同轴静电纺丝后制得核壳型碳纤维,再经氧化及碳化处理后得到具有空心结构且内部装载有保温剂的的复合纤维。然后将所得复合纤维浸入二氧化钛溶胶中,待浸渍完毕,将其取出并进行煅烧处理,从而在复合纤维的表面沉积了大量的纳米二氧化钛,制得改性复合纤维。然后依次对改性复合纤维进行羟基化及巯基化,从而在其表面引入活性反应基团,制得纤维载体,为后续功能助剂的制备奠定了理论基础。再者,保温剂以硝酸铈、溴酸钾及2-氨基-3-氨基甲酰丙酸为原料,制得具有空心球形形貌的纳米二氧化铈,即保温剂。由于保温剂装载在空心结构的核壳型碳纤维的内部,两者相互协同使得所制备的功能助剂具有优异的保温效果,使得所制备的软瓷装饰材料具有优异的保温性能。同时,核壳型碳纤维还能有效地提升软瓷装饰材料的力学性能,有效地保证了其品质。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of building decoration materials technology, specifically to an antibacterial thermal insulation soft ceramic decorative material and its preparation method. Background Technology
[0002] Flexible ceramic tiles (also known as flexible facing tiles) are a new type of building decoration material. With their advantages of being lightweight, flexible, weather-resistant, and easy to install, they are gradually replacing traditional ceramic tiles and paints, and are widely used in interior and exterior wall decoration. However, as people's requirements for living environments increase, simple decorative functions can no longer meet market demands. Especially in public buildings, medical facilities, and humid areas, the antibacterial properties of wall materials are crucial to prevent bacterial growth and cross-infection. At the same time, under the background of energy conservation and emission reduction, improving the thermal insulation performance of buildings is also a key focus of industry development.
[0003] In existing technologies, improving the antibacterial properties of flexible ceramic decorative materials often involves adding inorganic metal ions such as silver and copper, or loading organic antibacterial agents. However, inorganic antibacterial agents (such as silver-based agents) are expensive and prone to oxidation and discoloration during use, affecting the decorative effect. Organic antibacterial agents generally suffer from poor heat resistance, poor compatibility with the matrix, and easy migration from the interior of the flexible ceramic decorative material to the surface during use, leading to a significant decrease in antibacterial effect over time. Regarding improving thermal insulation performance, traditional methods involve adding hollow glass microspheres, expanded perlite, or creating a porous structure through foaming processes. However, these methods often sacrifice the mechanical properties of the flexible ceramic decorative material: adding large amounts of thermal insulation fillers can worsen its mechanical properties, thus affecting product quality.
[0004] Therefore, the present invention provides an antibacterial heat-insulating soft ceramic decorative material and its preparation method to solve the above-mentioned technical problems. Summary of the Invention
[0005] This invention provides an antibacterial thermal insulation flexible ceramic decorative material and its preparation method. The prepared flexible ceramic decorative material not only has excellent antibacterial and thermal insulation properties, but also has good mechanical properties. It effectively ensures its quality and, to a certain extent, solves the technical problem of shortened service life caused by microbial erosion.
[0006] To achieve the above objectives, the present invention provides the following technical solution: An antibacterial, heat-insulating, flexible ceramic decorative material is made from the following components by weight: 50-70 parts ceramic slag, 15-20 parts palladium powder, 5-10 parts vermiculite powder, 1-2.5 parts expanded graphite, 2-5 parts silica sol, 8-15 parts magnesium hydroxide, 2-3 parts silane coupling agent KH550, 5-8 parts functional additives, 0.5-0.8 parts sodium dodecyl sulfate, 0.8-1.2 parts sodium carboxymethyl cellulose, and an appropriate amount of water.
[0007] Furthermore, the preparation method of the functional additive is as follows: Step 1: Add diphenyl-2-propenylphosphine and 1,8-dichlorooctane to chloroform at a molar ratio of 1:1.2-1.4 in a mass ratio of 10-15 times that of diphenyl-2-propenylphosphine. Stir the reaction mixture at 50-60°C for 2-3 hours under nitrogen protection. Filter the reaction mixture and wash the filter cake 3-5 times with anhydrous ethanol. Then, vacuum dry the filter cake at 50-70°C for 5-8 hours to obtain the modifier. Step 2: Add 15-25% (by weight of the fiber carrier) of modifier and 8-12% (by weight of the modifier) of benzoin dimethyl ether to a 50-100 g / L fiber carrier dispersion, and heat at 550 mW / cm 2 Under the action of ultraviolet light, the reaction is carried out at a temperature of 40-50℃ for 30-40 minutes; then the reaction solution is filtered, washed and dried to obtain the functional additive. The fiber carrier dispersion also contains 5-8 wt% dodecyltrimethylammonium chloride, and the solvent used in the fiber carrier dispersion is a mixture of water and N,N-dimethylformamide in a volume ratio of 1:1-2. The fiber carrier is prepared by using modified composite fibers with nano-titanium dioxide loaded on the surface as the matrix material, and then undergoing hydroxylation and mercaptolation treatments in sequence.
[0008] Furthermore, the preparation method of the modified composite fiber is as follows: Tetrabutyl titanate and anhydrous ethanol are thoroughly mixed at a mass ratio of 1:3-4 to obtain a reaction solution; anhydrous ethanol, glacial acetic acid, and distilled water are uniformly mixed at a mass ratio of 2.5-3.0:1-1.5:1 to obtain a mixed solution; while stirring, the mixed solution is added dropwise to the reaction solution at 30-35℃, and after the addition is complete, stirring is continued for 1-2 hours to obtain titanium dioxide sol; then the composite fiber is immersed in the titanium dioxide sol, stirred for 50-80 minutes, the composite fiber is removed and spun dry, dried at 70-80℃, and calcined at 450-500℃ for 2-3 hours under nitrogen protection, and then naturally cooled to room temperature to obtain the final product; wherein, the mass ratio of distilled water to tetrabutyl titanate is 1:1.8-2.3.
[0009] Furthermore, the preparation method of the composite fiber is as follows: polyacrylonitrile is dissolved in N,N-dimethylformamide at 60-75℃ to obtain a first solution; the heat-insulating agent, N,N-dimethylformamide and polystyrene-acrylonitrile copolymer are stirred and dissolved completely at 60-80℃ in a mass ratio of 1:15-25:5-8 to obtain a second solution; then, the first solution is used as the shell layer and the second solution is used as the core layer, and the core-shell carbon fiber is obtained by coaxial electrospinning, and then obtained by oxidation and carbonization treatment.
[0010] Furthermore, during the electrospinning process, a No. 23 needle is used for the core layer solution, with a solution advance speed of 0.5-1.5 mL / h; a No. 17 needle is used for the shell layer solution, with a solution advance speed of 1-2 mL / h, a voltage of 15-25 kV, and a distance of 15-25 cm between the needle and the receiver.
[0011] Furthermore, the preparation method of the heat-insulating agent is as follows: add potassium bromate in molar amounts of 8-12 times that of cerium nitrate and 2-amino-3-carbamoylpropionic acid in molar amounts of 3-5 times that of cerium nitrate to a 0.3-0.8 mol / L aqueous solution of cerium nitrate, react at 130-150℃ for 20-30 h, and then naturally cool to room temperature. After filtration, washing, vacuum drying and calcination are performed sequentially to obtain the heat-insulating agent.
[0012] Furthermore, the hydroxylation treatment method for modified composite fibers is as follows: the modified composite fibers are immersed in hydrogen peroxide at a temperature of 70-80℃ and a concentration of 10-20wt% for 50-90 minutes at a mass ratio of 1:10-15, and then filtered out, washed and dried.
[0013] Furthermore, the method for thiolizing the modified composite fiber is as follows: the hydroxylated modified composite fiber, 85-90wt% ethanol aqueous solution and 3-mercaptopropyltrimethoxysilane are uniformly mixed at a mass ratio of 1:20-30:0.6-1, and the mixture is stirred at 60-70℃ for 3-4 hours. The reaction solution is then filtered, washed and dried in sequence.
[0014] Furthermore, the oxidation method is as follows: heat to 200-300℃ at a rate of 5-10℃ / min, and hold for 1-3 hours. The carbonization method includes heating to 600-800℃ in a nitrogen atmosphere at a rate of 5-15℃ / min, and holding the temperature for 2-5 hours.
[0015] A method for preparing an antibacterial thermal insulation flexible ceramic decorative material includes the following steps: Step 1: Weigh each raw material according to the formula, and mix ceramic slag, attapulgite powder, vermiculite powder, expanded graphite and functional additives evenly. Then add silica sol, silane coupling agent KH550 and water with a mass of 8-12 times that of ceramic slag. Mix and stir evenly to obtain a mixed liquid. Step 2: Mix sodium dodecyl sulfate and magnesium hydroxide and stir for 40-60 minutes. Then add sodium carboxymethyl cellulose and water with a mass of 10-15 times that of magnesium hydroxide, and mix and stir at a speed of 130-160 r / min for 5-10 minutes to obtain the foaming component. The third step involves mixing the liquid mixture and foaming components at a rate of 120-150 r / min for 40-60 minutes, allowing it to stand and defoam until a paste is formed, and then sequentially undergoing molding, secondary standing, and dehydration treatments to obtain the antibacterial thermal insulation soft ceramic decorative material.
[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses polyacrylonitrile, a thermal insulation agent, and polystyrene-acrylonitrile copolymer as raw materials. Core-shell carbon fibers are prepared through coaxial electrospinning, followed by oxidation and carbonization treatments to obtain composite fibers with a hollow structure and internally loaded with a thermal insulation agent. The resulting composite fibers are then immersed in titanium dioxide sol. After impregnation, they are removed and calcined, resulting in the deposition of a large amount of nano-titanium dioxide on the surface of the composite fibers, thus obtaining modified composite fibers. The modified composite fibers are then sequentially hydroxylated and thiolized to introduce active reactive groups onto their surface, obtaining a fiber carrier and laying the theoretical foundation for the subsequent preparation of functional additives. Furthermore, the thermal insulation agent is prepared from cerium nitrate, potassium bromate, and 2-amino-3-carbamoylpropionic acid to obtain nano-cerium dioxide with a hollow spherical morphology. Since the thermal insulation agent is loaded inside the hollow core-shell carbon fibers, the two work synergistically to give the prepared functional additives excellent thermal insulation effects, resulting in excellent thermal insulation performance in the prepared soft ceramic decorative materials. Meanwhile, core-shell carbon fiber can effectively improve the mechanical properties of flexible ceramic decorative materials, thus effectively ensuring their quality.
[0017] 2. This invention uses diphenyl-2-propenylphosphine and 1,8-dichlorooctane as raw materials to prepare an antibacterial compound containing unsaturated bonds, i.e., a modifier, through a chemical reaction. A fiber carrier is uniformly dispersed in a dispersion containing dodecyltrimethylammonium chloride, allowing the dodecyltrimethylammonium chloride to be uniformly adsorbed onto the surface of the fiber carrier. Then, under the action of benzoin dimethyl ether and ultraviolet light, the modifier reacts chemically with the active groups on the fiber carrier to form bonds, ultimately forming a crisscrossing and dense "three-dimensional antibacterial envelope layer" on the surface of the fiber carrier. This "three-dimensional antibacterial envelope layer" effectively confines the dodecyltrimethylammonium chloride to the surface of the fiber carrier, reducing its migration probability. Finally, through the synergistic effect of the "three-dimensional antibacterial envelope layer," nano-titanium dioxide, and dodecyltrimethylammonium chloride, the prepared soft ceramic decorative material exhibits excellent and long-lasting antibacterial properties.
[0018] In summary, the soft ceramic decorative material prepared by this invention not only has excellent antibacterial and thermal insulation properties, but also has good mechanical properties. It effectively ensures its quality and, to a certain extent, solves the technical problem of shortened service life caused by microbial erosion. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] The relevant information of the raw materials used in the following examples is as follows: The ceramic slag is a solid waste residue generated during the edge grinding and polishing process in the production of ceramic bricks; its particle size is 100-400 mesh, and its composition is SiO2: 50-70wt%, Al2O3: 10-30wt%, MgO: 2-5wt%, CaO: 2-4wt%, K2O: 2-6%, Na2O: 2-8%; the particle size of the attapulgite powder is 50-200 mesh; the particle size of the expanded graphite is 300-500 mesh; the particle size of the vermiculite powder is 0.3-0.8mm, the SiO2 content is 38-40%, and the Al2O3 mass content is 13-15%; the SiO2 content in the silica sol is 20-30wt%, the particle size distribution is 5-20nm, and the pH value is 8.5-10.0; the average particle size of the thermal insulation agent is 90-120nm; and the length of the composite fiber is 5-10mm. Example 1:
[0021] An antibacterial thermal insulation soft ceramic decorative material is made from the following components by weight: 50 parts ceramic slag, 15 parts palladium powder, 5 parts vermiculite powder, 1 part expanded graphite, 2 parts silica sol, 8 parts magnesium hydroxide, 2 parts silane coupling agent KH550, 5 parts functional additives, 0.5 parts sodium dodecyl sulfate, 0.8 parts sodium carboxymethyl cellulose and appropriate amount of water; Among them, the particle size of ceramic slag is 100 mesh; the particle size of attapulgite powder is 50 mesh; the particle size of expanded graphite is 300 mesh; the particle size of vermiculite powder is 0.3 mm; the silica sol is alkaline sodium silica sol, and the content of SiO2 in the silica sol is 20 wt%, the pH value is 8.5; and the length of the composite fiber is 5 mm.
[0022] The preparation method of the functional additive is as follows: Step 1: Diphenyl-2-propenylphosphine and 1,8-dichlorooctane were added to chloroform at a molar ratio of 1:1.2 in a mass of 10 times that of diphenyl-2-propenylphosphine. The mixture was stirred at 50°C for 3 hours under nitrogen protection. The reaction solution was then filtered, and the filter cake was washed three times with anhydrous ethanol and then dried under vacuum at 50°C for 8 hours to obtain the modifier. Step 2: Add 15% (by weight of the fiber carrier) of the modifier and 8% (by weight of the modifier) of benzoin dimethyl ether to a 50 g / L fiber carrier dispersion, and heat at 550 mW / cm 2Under the action of ultraviolet light, the reaction was carried out at a temperature of 40°C for 40 minutes; then the reaction solution was filtered, washed and dried to obtain the functional additive. The fiber carrier dispersion also contains 5 wt% dodecyltrimethylammonium chloride, and the solvent used in the fiber carrier dispersion is a mixture of water and N,N-dimethylformamide in a 1:1 volume ratio. The fiber carrier is prepared by using modified composite fibers with nano-titanium dioxide loaded on the surface as the matrix material, and then undergoing hydroxylation and mercaptolation treatments in sequence.
[0023] The modified composite fiber is prepared as follows: Tetrabutyl titanate and anhydrous ethanol are thoroughly mixed at a mass ratio of 1:3 to obtain a reaction solution; anhydrous ethanol, glacial acetic acid, and distilled water are uniformly mixed at a mass ratio of 2.5:1:1 to obtain a mixed solution; the mixed solution is added dropwise to the reaction solution at 30°C while stirring, and stirring is continued for 2 hours after the addition is complete to obtain titanium dioxide sol; then the composite fiber is immersed in the titanium dioxide sol, stirred for 50 minutes, the composite fiber is removed and spun dry, dried at 70°C, and calcined at 450°C for 3 hours under nitrogen protection, and then naturally cooled to room temperature to obtain the final product; wherein, the mass ratio of distilled water to tetrabutyl titanate is 1:1.8.
[0024] The preparation method of composite fibers is as follows: Polyacrylonitrile is dissolved in N,N-dimethylformamide at 60℃ to obtain a first solution; thermal insulation agent, N,N-dimethylformamide and polystyrene-acrylonitrile copolymer are stirred and dissolved completely at 60℃ in a mass ratio of 1:15:5 to obtain a second solution; then, core-shell carbon fibers are prepared by coaxial electrospinning with the first solution as the shell layer and the second solution as the core layer, and then subjected to oxidation and carbonization treatment to obtain the final product. The oxidation method is as follows: heat the temperature to 200℃ at a rate of 5℃ / min and keep it at that temperature for 3 hours. The carbonization method includes heating to 600°C at a rate of 5°C / min in a nitrogen atmosphere and holding the temperature for 5 hours.
[0025] During electrospinning, a No. 23 needle was used for the core solution, with a solution advance speed of 0.5 mL / h; a No. 17 needle was used for the shell solution, with a solution advance speed of 1 mL / h, a voltage of 15 kV, and a distance of 15 cm between the needle and the receiver.
[0026] The heat-insulating agent is prepared by adding potassium bromate (8 times the molar amount of cerium nitrate) and 2-amino-3-carbamoylpropionic acid (3 times the molar amount of cerium nitrate) to a 0.3 mol / L aqueous solution of cerium nitrate. After reacting at 130℃ for 30 h, the solution is naturally cooled to room temperature and then subjected to filtration, washing, vacuum drying and calcination.
[0027] The hydroxylation treatment method for modified composite fibers is as follows: the modified composite fibers are immersed in hydrogen peroxide at a temperature of 70℃ and a concentration of 10wt% for 90 minutes at a mass ratio of 1:10, then filtered out, washed and dried.
[0028] The method for thiolizing modified composite fibers is as follows: hydroxylated modified composite fibers, 85wt% ethanol aqueous solution and 3-mercaptopropyltrimethoxysilane are uniformly mixed at a mass ratio of 1:20:0.6, stirred and reacted at 60℃ for 4 hours, and then the reaction solution is filtered, washed and dried in sequence.
[0029] A method for preparing an antibacterial thermal insulation flexible ceramic decorative material includes the following steps: Step 1: Weigh each raw material according to the formula, and mix ceramic slag, attapulgite powder, vermiculite powder, expanded graphite and functional additives evenly. Then add silica sol, silane coupling agent KH550 and water with a mass of 10 times that of ceramic slag. Mix and stir evenly to obtain a mixed liquid. Step 2: Mix sodium dodecyl sulfate and magnesium hydroxide for 40 minutes, then add sodium carboxymethyl cellulose and water with a mass of 10 times that of magnesium hydroxide, and mix and stir at 150 r / min for 5 minutes to obtain the foaming component; The third step involves mixing the liquid mixture and foaming components at a rate of 130 r / min for 50 minutes, allowing it to stand and defoam until a paste is formed, and then sequentially undergoing molding, secondary standing, and dehydration treatments to obtain the antibacterial thermal insulation soft ceramic decorative material. Example 2:
[0030] The preparation method of the antibacterial thermal insulation soft ceramic decorative material provided in this embodiment is basically the same as that in Example 1, except that the specific proportions of the raw materials and the preparation methods of the functional additives are different. The specific proportions of the raw materials and the preparation methods of the functional additives in this embodiment are as follows: An antibacterial, heat-insulating, flexible ceramic decorative material is made from the following components by weight: 60 parts ceramic slag, 20 parts palladium powder, 8 parts vermiculite powder, 2 parts expanded graphite, 3 parts silica sol, 10 parts magnesium hydroxide, 3 parts silane coupling agent KH550, 6 parts functional additives, 0.6 parts sodium dodecyl sulfate, 1.0 part sodium carboxymethyl cellulose, and an appropriate amount of water; Among them, the particle size of ceramic slag is 300 mesh; the particle size of attapulgite powder is 200 mesh; the particle size of expanded graphite is 400 mesh; the particle size of vermiculite powder is 0.6 mm; the silica sol is alkaline sodium silica sol, and the content of SiO2 in the silica sol is 25 wt%, the pH value is 9.0; and the length of the composite fiber is 8 mm.
[0031] The preparation method of the functional additive is as follows: Step 1: Diphenyl-2-propenylphosphine and 1,8-dichlorooctane were added to chloroform at a molar ratio of 1:1.3 in a mass of 15 times that of diphenyl-2-propenylphosphine. The mixture was stirred at 55°C for 3 hours under nitrogen protection. The reaction solution was then filtered, and the filter cake was washed four times with anhydrous ethanol and then dried under vacuum at 60°C for 6 hours to obtain the modifier. Step 2: Add 20% (by weight of the fiber carrier) of the modifier and 10% (by weight of the modifier) of benzoin dimethyl ether to the 80 g / L fiber carrier dispersion, and heat at 550 mW / cm 2 Under the action of ultraviolet light, the reaction was carried out at a temperature of 45℃ for 35 minutes; then the reaction solution was filtered, washed and dried to obtain the functional additive. The fiber carrier dispersion also contains 6 wt% dodecyltrimethylammonium chloride, and the solvent used in the fiber carrier dispersion is a mixture of water and N,N-dimethylformamide in a volume ratio of 1:2. The fiber carrier is prepared by using modified composite fibers with nano-titanium dioxide loaded on the surface as the matrix material, and then undergoing hydroxylation and mercaptolation treatments in sequence.
[0032] The modified composite fiber is prepared as follows: Tetrabutyl titanate and anhydrous ethanol are thoroughly mixed at a mass ratio of 1:4 to obtain a reaction solution; anhydrous ethanol, glacial acetic acid, and distilled water are uniformly mixed at a mass ratio of 3.0:1.5:1 to obtain a mixed solution; the mixed solution is added dropwise to the reaction solution at 35°C while stirring, and stirring is continued for 1 hour after the addition is complete to obtain titanium dioxide sol; then the composite fiber is immersed in the titanium dioxide sol, stirred for 60 minutes, the composite fiber is removed and spun dry, dried at 75°C, and calcined at 500°C for 2 hours under nitrogen protection, and then naturally cooled to room temperature to obtain the final product; wherein, the mass ratio of distilled water to tetrabutyl titanate is 1:2.
[0033] The preparation method of composite fiber is as follows: Polyacrylonitrile is dissolved in N,N-dimethylformamide at 70℃ to obtain a first solution; thermal insulation agent, N,N-dimethylformamide and polystyrene-acrylonitrile copolymer are stirred and dissolved completely at 70℃ in a mass ratio of 1:20:7 to obtain a second solution; then, core-shell carbon fiber is prepared by coaxial electrospinning with the first solution as the shell layer and the second solution as the core layer, and then subjected to oxidation and carbonization treatment to obtain the final product. The oxidation method is as follows: heat the temperature to 250℃ at a rate of 10℃ / min and hold it at that temperature for 2 hours. The carbonization method includes heating to 700°C at a rate of 10°C / min in a nitrogen atmosphere and holding the temperature for 4 hours.
[0034] During electrospinning, a No. 23 needle was used for the core layer solution, with a solution advance speed of 1.0 mL / h; a No. 17 needle was used for the shell layer solution, with a solution advance speed of 1.5 mL / h, a voltage of 20 kV, and a distance of 20 cm between the needle and the receiver.
[0035] The heat-insulating agent is prepared by adding potassium bromate (10 times the molar amount of cerium nitrate) and 2-amino-3-carbamoylpropionic acid (4 times the molar amount of cerium nitrate) to a 0.5 mol / L aqueous solution of cerium nitrate. After reacting at 140℃ for 25 h, the solution is naturally cooled to room temperature and then subjected to filtration, washing, vacuum drying and calcination.
[0036] The hydroxylation treatment method for modified composite fibers is as follows: the modified composite fibers are immersed in hydrogen peroxide at a temperature of 75℃ and a concentration of 15wt% for 80 minutes at a mass ratio of 1:15, then filtered out, washed and dried.
[0037] The method for thiolizing modified composite fibers is as follows: hydroxylated modified composite fibers, 90wt% ethanol aqueous solution and 3-mercaptopropyltrimethoxysilane are uniformly mixed at a mass ratio of 1:25:0.8, stirred and reacted at 65℃ for 4 hours, and then the reaction solution is filtered, washed and dried in sequence. Example 3:
[0038] The preparation method of the antibacterial thermal insulation soft ceramic decorative material provided in this embodiment is basically the same as that in Example 1, except that the specific proportions of the raw materials and the preparation methods of the functional additives are different. The specific proportions of the raw materials and the preparation methods of the functional additives in this embodiment are as follows: An antibacterial thermal insulation soft ceramic decorative material is made from the following components by weight: 70 parts ceramic slag, 20 parts palladium powder, 10 parts vermiculite powder, 2.5 parts expanded graphite, 5 parts silica sol, 15 parts magnesium hydroxide, 3 parts silane coupling agent KH550, 8 parts functional additives, 0.8 parts sodium dodecyl sulfate, 1.2 parts sodium carboxymethyl cellulose and appropriate amount of water; Among them, the particle size of ceramic slag is 400 mesh; the particle size of attapulgite powder is 200 mesh; the particle size of expanded graphite is 500 mesh; the particle size of vermiculite powder is 0.8 mm; the silica sol is alkaline sodium silica sol, and the content of SiO2 in the silica sol is 30 wt%, the pH value is 10.0; and the length of the composite fiber is 10 mm.
[0039] The preparation method of the functional additive is as follows: Step 1: Diphenyl-2-propenylphosphine and 1,8-dichlorooctane were added to chloroform at a molar ratio of 1:1.4 in a mass of 15 times that of diphenyl-2-propenylphosphine. The mixture was stirred at 60°C for 2 hours under nitrogen protection. The reaction solution was then filtered, and the filter cake was washed 5 times with anhydrous ethanol and then dried under vacuum at 70°C for 5 hours to obtain the modifier. Step 2: Add 25% (by weight of the fiber carrier) of the modifier and 12% (by weight of the modifier) of benzoin dimethyl ether to a 100 g / L fiber carrier dispersion, and heat at 550 mW / cm 2 Under the action of ultraviolet light, the reaction was carried out at a temperature of 50°C for 30 minutes; then the reaction solution was filtered, washed and dried to obtain the functional additive. The fiber carrier dispersion also contains 8 wt% dodecyltrimethylammonium chloride, and the solvent used in the fiber carrier dispersion is a mixture of water and N,N-dimethylformamide in a volume ratio of 1:2. The fiber carrier is prepared by using modified composite fibers with nano-titanium dioxide loaded on the surface as the matrix material, and then undergoing hydroxylation and mercaptolation treatments in sequence.
[0040] The modified composite fiber is prepared as follows: Tetrabutyl titanate and anhydrous ethanol are thoroughly mixed at a mass ratio of 1:4 to obtain a reaction solution; anhydrous ethanol, glacial acetic acid, and distilled water are uniformly mixed at a mass ratio of 3.0:1.5:1 to obtain a mixed solution; the mixed solution is added dropwise to the reaction solution at 35°C while stirring, and stirring is continued for 1 hour after the addition is complete to obtain titanium dioxide sol; then the composite fiber is immersed in the titanium dioxide sol, stirred for 80 minutes, the composite fiber is removed and spun dry, dried at 80°C, and calcined at 500°C for 2 hours under nitrogen protection, and then naturally cooled to room temperature to obtain the final product; wherein, the mass ratio of distilled water to tetrabutyl titanate is 1:2.3.
[0041] The preparation method of composite fiber is as follows: Polyacrylonitrile is dissolved in N,N-dimethylformamide at 75℃ to obtain a first solution; thermal insulation agent, N,N-dimethylformamide and polystyrene-acrylonitrile copolymer are stirred and dissolved completely at 80℃ in a mass ratio of 1:25:8 to obtain a second solution; then, core-shell carbon fiber is prepared by coaxial electrospinning with the first solution as the shell layer and the second solution as the core layer, and then subjected to oxidation and carbonization treatment to obtain the final product. The oxidation method is as follows: heat the temperature to 300℃ at a rate of 10℃ / min and hold it at that temperature for 1 hour. The carbonization method includes heating to 800°C at a rate of 15°C / min in a nitrogen atmosphere and holding the temperature for 2 hours.
[0042] During electrospinning, a No. 23 needle was used for the core layer solution, with a solution advance speed of 1.5 mL / h; a No. 17 needle was used for the shell layer solution, with a solution advance speed of 2 mL / h, a voltage of 25 kV, and a distance of 25 cm between the needle and the receiver.
[0043] The heat-insulating agent is prepared by adding potassium bromate (12 times the molar amount of cerium nitrate) and 2-amino-3-carbamoylpropionic acid (5 times the molar amount of cerium nitrate) to a 0.8 mol / L aqueous solution of cerium nitrate. After reacting at 150℃ for 20 h, the solution is naturally cooled to room temperature and then subjected to filtration, washing, vacuum drying and calcination.
[0044] The hydroxylation treatment method for modified composite fibers is as follows: soak the modified composite fibers in hydrogen peroxide at a temperature of 80℃ and a concentration of 20wt% for 50 minutes at a mass ratio of 1:15, then filter them out, wash and dry them.
[0045] The method for thiolizing modified composite fibers is as follows: hydroxylated modified composite fibers, 90wt% ethanol aqueous solution and 3-mercaptopropyltrimethoxysilane are uniformly mixed at a mass ratio of 1:30:1, stirred and reacted at 70℃ for 3h, and then the reaction solution is filtered, washed and dried in sequence.
[0046] Comparative Example 1: The difference between this comparative example and Example 1 is that the fiber carrier dispersion used in this comparative example does not contain dodecyltrimethylammonium chloride.
[0047] Comparative Example 2: The difference between this comparative example and Example 1 is that an equal amount of modified composite fiber is used to replace the functional additives in this comparative example.
[0048] Comparative Example 3: The difference between this comparative example and Example 1 is that an equal amount of composite fiber is used to replace the functional additives in this comparative example.
[0049] Comparative Example 4: The difference between this comparative example and Example 1 is that the second solution used in the preparation of composite fibers in this comparative example does not contain a heat-insulating agent.
[0050] Comparative Example 5: The difference between this comparative example and Example 1 is that the functional additives are replaced with an equal amount of solid carbon fiber of the same specifications as in Example 1.
[0051] Comparative Example 6: The difference between this comparative example and Example 1 is that the "functional additive" used in this comparative example did not use a grafting modifier. Instead, the fiber carrier was dispersed in a fiber carrier dispersion of the same concentration as in Example 1, and after uniform dispersion, it was immersed for 2-3 hours and then dried. Furthermore, the amount of "functional additive" used in this example is the same as that used in the example.
[0052] Performance testing: The relevant properties of the soft ceramic decorative material samples prepared in Examples 1-3 and Comparative Examples 1-6 were tested as follows, and the test data are recorded in Tables 1 and 2: 1. Tensile strength and bending strength: Tensile strength, elongation at break and bending strength are tested using a tensile strength tester.
[0053] 2. Thermal conductivity: The test was conducted in accordance with GB / T10294-2008 "Determination of steady-state thermal resistance and related properties of thermal insulation materials by protective hot plate method", and the thermal conductivity tester used was the HS-DR-1 thermal conductivity tester manufactured by Shanghai Hesheng Instrument Technology Co., Ltd.
[0054] 3. Antibacterial properties: The antibacterial properties were tested according to the JC / T 897-2014 standard.
[0055] Table 1
[0056] Table 2
[0057] By comparing and analyzing the relevant data in Tables 1 and 2, it can be seen that the flexible ceramic decorative material prepared by this invention not only has excellent antibacterial and thermal insulation properties, but also good mechanical properties. This effectively ensures its quality while also solving, to some extent, the technical problem of shortened service life due to microbial erosion. Therefore, this indicates that the antibacterial thermal insulation flexible ceramic decorative material and its preparation method provided by this invention have a broader market prospect and are more suitable for widespread application.
[0058] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0059] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. An antibacterial, heat-insulating, flexible ceramic decorative material, characterized in that, It is made from the following components by weight: 50-70 parts ceramic slag, 15-20 parts palygorskite powder, 5-10 parts vermiculite powder, 1-2.5 parts expanded graphite, 2-5 parts silica sol, 8-15 parts magnesium hydroxide, 2-3 parts silane coupling agent KH550, 5-8 parts functional additives, 0.5-0.8 parts sodium dodecyl sulfate, 0.8-1.2 parts sodium carboxymethyl cellulose and appropriate amount of water.
2. The antibacterial thermal insulation flexible ceramic decorative material according to claim 1, characterized in that, The preparation method of the functional additive is as follows: Step 1: Add diphenyl-2-propenylphosphine and 1,8-dichlorooctane to chloroform at a molar ratio of 1:1.2-1.4 in a mass ratio of 10-15 times that of diphenyl-2-propenylphosphine. Stir the reaction mixture at 50-60°C for 2-3 hours under nitrogen protection. Filter the reaction mixture and wash the filter cake 3-5 times with anhydrous ethanol. Then, vacuum dry the filter cake at 50-70°C for 5-8 hours to obtain the modifier. Step 2: Add 15-25% (by weight of the fiber carrier) of modifier and 8-12% (by weight of the modifier) of benzoin dimethyl ether to a 50-100 g / L fiber carrier dispersion, and heat at 550 mW / cm 2 Under the action of ultraviolet light, the reaction is carried out at a temperature of 40-50℃ for 30-40 minutes; then the reaction solution is filtered, washed and dried to obtain the functional additive. The fiber carrier dispersion also contains 5-8 wt% dodecyltrimethylammonium chloride, and the solvent used in the fiber carrier dispersion is a mixture of water and N,N-dimethylformamide in a volume ratio of 1:1-2. The fiber carrier is prepared by using modified composite fibers with nano-titanium dioxide loaded on the surface as the matrix material, and then undergoing hydroxylation and mercaptolation treatments in sequence.
3. The antibacterial thermal insulation flexible ceramic decorative material according to claim 2, characterized in that, The modified composite fiber is prepared as follows: Tetrabutyl titanate and anhydrous ethanol are thoroughly mixed at a mass ratio of 1:3-4 to obtain a reaction solution; anhydrous ethanol, glacial acetic acid, and distilled water are uniformly mixed at a mass ratio of 2.5-3.0:1-1.5:1 to obtain a mixed solution; while stirring, the mixed solution is added dropwise to the reaction solution at 30-35℃, and stirring is continued for 1-2 hours after the addition is complete to obtain titanium dioxide sol; then the composite fiber is immersed in the titanium dioxide sol, stirred for 50-80 minutes, and then the composite fiber is removed and spun dry, dried at 70-80℃, and calcined at 450-500℃ for 2-3 hours under nitrogen protection, and then naturally cooled to room temperature to obtain the final product; wherein, the mass ratio of distilled water to tetrabutyl titanate is 1:1.8-2.
3.
4. The antibacterial thermal insulation flexible ceramic decorative material according to claim 3, characterized in that, The composite fiber is prepared as follows: polyacrylonitrile is dissolved in N,N-dimethylformamide at 60-75℃ to obtain a first solution; thermal insulation agent, N,N-dimethylformamide and polystyrene-acrylonitrile copolymer are dissolved completely at 60-80℃ in a mass ratio of 1:15-25:5-8 to obtain a second solution; then, core-shell carbon fiber is prepared by coaxial electrospinning with the first solution as the shell and the second solution as the core, and then obtained by oxidation and carbonization treatment.
5. The antibacterial thermal insulation flexible ceramic decorative material according to claim 4, characterized in that, During electrospinning, a No. 23 needle is used for the core layer solution, with a solution advance speed of 0.5-1.5 mL / h; a No. 17 needle is used for the shell layer solution, with a solution advance speed of 1-2 mL / h, a voltage of 15-25 kV, and a distance of 15-25 cm between the needle and the receiver.
6. The antibacterial thermal insulation flexible ceramic decorative material according to claim 4, characterized in that, The heat-insulating agent is prepared by adding potassium bromate (8-12 times the molar amount of cerium nitrate) and 2-amino-3-carbamoylpropionic acid (3-5 times the molar amount of cerium nitrate) to a 0.3-0.8 mol / L aqueous solution of cerium nitrate. After reacting at 130-150℃ for 20-30 h, the mixture is naturally cooled to room temperature and then subjected to filtration, washing, vacuum drying, and calcination to obtain the final product.
7. The antibacterial thermal insulation flexible ceramic decorative material according to claim 2, characterized in that, The hydroxylation treatment method for modified composite fibers is as follows: immerse the modified composite fibers in hydrogen peroxide at a temperature of 70-80℃ and a concentration of 10-20wt% for 50-90 minutes at a mass ratio of 1:10-15, then filter them out, wash and dry them.
8. The antibacterial thermal insulation flexible ceramic decorative material according to claim 2, characterized in that, The method for thiolizing modified composite fibers is as follows: hydroxylated modified composite fibers, 85-90wt% ethanol aqueous solution and 3-mercaptopropyltrimethoxysilane are uniformly mixed at a mass ratio of 1:20-30:0.6-1 and stirred at 60-70℃ for 3-4 hours. The reaction solution is then filtered, washed and dried sequentially.
9. The antibacterial thermal insulation flexible ceramic decorative material according to claim 4, characterized in that, The oxidation method is as follows: heat to 200-300℃ at a rate of 5-10℃ / min, and hold for 1-3 hours. The carbonization method includes heating to 600-800℃ in a nitrogen atmosphere at a rate of 5-15℃ / min, and holding the temperature for 2-5 hours.
10. A method for preparing an antibacterial thermal insulation flexible ceramic decorative material according to any one of claims 1-9, characterized in that, Includes the following steps: Step 1: Weigh each raw material according to the formula, and mix ceramic slag, attapulgite powder, vermiculite powder, expanded graphite and functional additives evenly. Then add silica sol, silane coupling agent KH550 and water with a mass of 8-12 times that of ceramic slag. Mix and stir evenly to obtain a mixed liquid. Step 2: Mix sodium dodecyl sulfate and magnesium hydroxide and stir for 40-60 minutes. Then add sodium carboxymethyl cellulose and water with a mass of 10-15 times that of magnesium hydroxide, and mix and stir at a speed of 130-160 r / min for 5-10 minutes to obtain the foaming component. The third step involves mixing the liquid mixture and foaming components at a rate of 120-150 r / min for 40-60 minutes, allowing it to stand and defoam until a paste is formed, and then sequentially undergoing molding, secondary standing, and dehydration treatments to obtain the antibacterial thermal insulation soft ceramic decorative material.